The Effect of Comprehensive Sexual Models on Self-Efficacy of Prevention of Sexual Violence in Adolescents at SMAN X Suwawa - Anindya Prananda Ishak; Nurdiana Djamaluddin; Nirwanto K. Rahim (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Adolescents are an age group that is vulnerable to sexual violence due to limited knowledge and ability to protect themselves. Self-efficacy plays an important role in shaping adolescents' confidence to carry out prevention. The comprehensive sexual education model is one of the educational approaches that can increase adolescents' self-efficacy through providing information and strengthening prevention skills. This study aims to determine the effect of the comprehensive sexual education model on the self-efficacy of sexual violence prevention in adolescents at SMAN X Suwawa. The study used a quantitative approach with a pre-experimental one-group pretest-posttest design and involved 61 respondents selected through cluster random sampling technique. The research instrument is in the form of a questionnaire in the form of a dichotomy question. The results showed that most adolescents experienced excellent self-efficacy (91.8%), while the rate of self-efficacy was good (8.2%) after being given intervention. The results of the Wilcoxon signed rank test showed a p-value = 0.006 (< 0.05), which indicates that there is a significant influence of the comprehensive sexual education model on the self-efficacy of preventing sexual violence in adolescents at SMAN X Suwawa. Schools are advised to integrate comprehensive sexuality education in learning activities and counseling guidance services.